Influence of mammal fossorial activity on bearing-out some chemical elements on up of soil cover - Pakhomov, Olexandr; Didur, Oleg; Loza, Iryna (Acta Agraria Debreceniensis, 2010)
Fossorial activity of mammals is conductive to trace of microelements from more deep soil horizons into zone of its active involving to biological cycle. As a result of researches have established the mostly intensive migration of micro- and macroelements that is goes at the expense of mammals fossorial activity it is typical for humid gully lime-and-ash with oak wood. A middle position in speed of entering chemical elements is belonging to artificial oak wood in the watershed and humid lime-and-ash with oak wood in floodplain. Mostly slow migration in speed of entering elements is typical for middle-dry pine wood on sandy terrace.